Selected attractiveness factors of academic conferences as a product on the international tourism market - Cieślikowski, Krzysztof; Brusokas, Andrius (Turyzm/Tourism, 2020)
The paper identifies selected determinants of attractiveness of international academic conferences as products on the contemporary international tourism market, especially on the business tourism market. To achieve this aim, methods of analysing the literature, reports, synthesis, along with passive and active observation were used. In addition, a direct survey using a research questionnaire via a website and addressed to participants on an Erasmus International Week in Kaunas was made. Some of the most important conditions of the attractiveness of the conference for participants, including transport and information accessibility as well as to the originality of the destination and the leisure program for participants, were indicated. Contemporary international academic conferences lasting a few days epitomize multiple products on tourism market. The article is empirical, but it also presents ideas for the development of conferences as attractive products in the contemporary economy of the European Union.